GREEN SKILLS FRAMEWORK FOR TVET STUDENTS IN THE CONSTRUCTION SECTOR - Azizi, Nor; A, Ismail; A. R, Abdul Razzaq; N. A. S., Sarif; S, Sutrisno (International Journal of Psychosocial Rehabilitation, 2020)
Environmental issues are social issues that are constantly affecting the society starting with environmental pollution, global climate change and the lack of natural resources that threatens the lives of individuals, communities, and other living organisms. The solution for the problem is to expose the public to green skills. Green skills are skills that need to be there for all ages and they underlie all areas. Individuals who enter the industry must be equipped with enough skills and knowledge related to green skills. But in Malaysia, green skills are still relatively new and need to be explored in terms of the types and forms of skills. Nowadays, individuals entering the industry do not have relevant qualifications. In this regard, this study was conducted to explore and develop the green skills framework for technical students in the construction sector. This study used qualitative approach, which data were collected through interviews conducted by three (3) experts who have served for over 5 years in the construction industry. Results from the interviews found 20 elements of green skills.